A review of wear mechanisms of ceramic-reinforced metal-matrix composite: case study of nano silica reinforced iron - Amir, Adibah; Mamat, Othman (Trans Tech Publications Ltd, 2011)
Available information on the composition and methods of production for particulate reinforced metal matrix composites (PRMMCs) for wear resistant applications is reviewed. In general, PRMMCs exhibit better wear resistance compared to its unreinforced counterparts. Nevertheless, under specified conditions, the wear performance of PRMMCs is similar to or lower than its respective alloy. Conflicting results were found among investigators with regards to different tribological parameters used in their investigations. A general framework was developed by identifying three parameters that affect the effectiveness of wear mechanisms model; fabrication method, types and characteristics of reinforcement and wear testing apparatus.